The Effect of Brief Stair-Climbing on Divergent and Convergent Thinking - Matsumoto, Karin; Chen, Chong; Hagiwara, Kosuke; Shimizu, Natsumi; Hirotsu, Masako; Oda, Yusuke; Lei, Huijie; Takao, Akiyo; Fujii, Yuko; Higuchi, Fumihiro; Nakagawa, Shin (Frontiers in Behavioral Neuroscience, 2022)
Recent studies show that even a brief bout of aerobic exercise may enhance creative thinking. However, few studies have investigated the effect of exercise conducted in natural settings. Here, in a crossover randomized controlled trial, we investigated the effect of a common daily activity, stair-climbing, on creative thinking. As experimental intervention, subjects were asked to walk downstairs from the fourth to the first floor and back at their usual pace. As control intervention, they walked the same path but using the elevator instead. Compared to using the elevator, stair-climbing enhanced subsequent divergent but not convergent thinking in that it increased originality on the Alternate Use Test (d=0.486). Subjects on average generated 61% more original uses after stair-climbing. This is the first study to investigate the effect of stair-climbing on creative thinking. Our findings suggest that stair-climbing may be a useful strategy for enhancing divergent thinking in everyday life.